HUBUNGAN PENGETAHUAN IBU HAMIL MENGENAI TANDA BAHAYA KEHAMILAN DENGAN PEMANFAATAN BUKU KESEHATAN IBU DAN ANAK (KIA) DI DESA DALAM KECAMATAN ALAS KABUPATEN SUMBAWA TAHUN 2021 - Sinta Ade Kantari; Uyunun Nudhira; Yunita Lestari (LPPM STIKES Griya Husada Sumbawa, 2021)
The indirect cause of maternal death is being late in knowing the danger signs of pregnancy. To be able to anticipate this, an effort is needed to be able to recognize pregnancy complications or danger signs of pregnancy. The purpose of this study was to determine the relationship between knowledge of pregnant women about the danger signs of pregnancy and the use of KIA books in Dalam Village, Alas District, Sumbawa Regency in 2021.The research used is an analytic survey with a cross sectional approach. The population in this study were 121 pregnant women and the sample of pregnant women in this study was 55 respondents. Data analysis was performed univariate and bivariate using chi-square.The results showed that the use of KIA books had a p value of (0.020 < 0.05), meaning that there was a relationship between knowledge of pregnant women about the dangers of using KIA books in Dalam Village, Alas District, Sumbawa Regency in 2021. The conclusion of the research is the relationship between knowledge of pregnant women about the danger signs of pregnancy and the use of KIA books in Dalam Village, Alas District, Sumbawa Regency in 2021. It is recommended to further increase the knowledge of pregnant women about pregnancy danger signs and the use of KIA books is a strategy for community empowerment, especially families to maintain their health and get quality maternal and child health services.